Foreign Direct Investment and Value Added in Indonesia - Fredrik Sjöholm (Lund University, School of Economics and Management, Department of Economics, 2016)
Foreign Direct Investment (FDI) has increased in importance over the last decades, globally as well as in Indonesia. We examine how such inflows of FDI affects value added in Indonesia. The effect is positive: foreign firms generate relatively high levels of value added and they also seem to have a positive impact on value added in local firms. Moreover, FDI contribute to a structural change of the economy towards more high-value added activities. High value added could lead to increased investments and higher tax revenues for the government. High value added could also benefit labor through higher wages, an effect that is empirically confirmed in Indonesia.
Keywords: F23; F61; F63; 330; Foreign Direct Investment; Multinational Firms; Value Added; Industrial Development